2015
DOI: 10.4103/0366-6999.164874
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Obstetric Anal Sphincter Injuries after Various Modes of Vaginal Deliveries in Chinese Women

Abstract: Background:Obstetric anal sphincter injuries (OASIS) can cause an adverse impact on women's physical and mental health. There was lack of published data in Chinese population particularly on studying the risk of OASIS for nonrotational outlet forceps. This study was to determine the incidence and risk factors of OASIS.Methods:This is a retrospective cohort study carried out in a tertiary referral hospital in Hong Kong. The control group was selected randomly. Univariate and multivariate logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…OASI rates are increasing in many countries. In the English National Health Service (NHS), reported OASI rates tripled among primiparous women over a decade, from 1.8% in 2000 to 5.9% in 2011, 3 with similar trends in many other countries 4–7 . The rise in OASI rates is likely to be linked to improved recognition of tears, changes in the characteristics of women giving birth as well as to changes in practice, such as an increased use of a ‘hands‐poised/hands‐off’ approach, opposed to a ‘hands‐on’ approach to protect the perineum, 8–10 a reluctance to perform an episiotomy 9 and gaps in the training of midwives and obstetricians 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…OASI rates are increasing in many countries. In the English National Health Service (NHS), reported OASI rates tripled among primiparous women over a decade, from 1.8% in 2000 to 5.9% in 2011, 3 with similar trends in many other countries 4–7 . The rise in OASI rates is likely to be linked to improved recognition of tears, changes in the characteristics of women giving birth as well as to changes in practice, such as an increased use of a ‘hands‐poised/hands‐off’ approach, opposed to a ‘hands‐on’ approach to protect the perineum, 8–10 a reluctance to perform an episiotomy 9 and gaps in the training of midwives and obstetricians 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…In China, episiotomy used to be a routine practice for vaginal delivery. 12 13 In the last decade, hospital data reported rates of 47.4%-84.7%, [14][15][16][17] and some multicentre studies reported hospital rates from 41.2% to 69.7%. 18 19 For China, where there were 17.23 million births in 2016, 20 there could be as many as 7.33 million episiotomies a year (given a vaginal birth rate of 61.0% and an episiotomy rate of 69.7% among vaginal births).…”
Section: Introductionmentioning
confidence: 99%
“…2 20 In China, episiotomy used to be a routine practice for vaginal delivery. In the last decade, hospital data reported rates of 47.4%-84.7%, [21][22][23] and some multicentre studies reported hospital rates of 41.2%-69.7%. 24 25 In China, there were 17.23 million births in 2016 26 and as many as 7.33 million women underwent an episiotomy a year (given a vaginal birth rate of 61% and an episiotomy rate of 69.7% among vaginal births).…”
Section: Open Accessmentioning
confidence: 99%